Impacts on water consumption of power sector in major emitting economies under INDC and longer term mitigation scenarios: An input-output based hybrid approach. (15th December 2016) - Wan, Liyang; Wang, Can; Cai, Wenjia
Highlights: Water consumptions of power sector are estimated by hybrid IO model. Impacts on water resources of power sector under INDC policy are analyzed. Significant additional water demand will be caused by China and India's INDC. The USA could benefit from power structural adjustment by water saving. Regional water scarcity needs be concerned for dramatic power structural changes. Abstract: Transformation of the energy sector's power generation mix is needed to contain global mean temperature rise to no more than 2 °C above the pre-industrial level. Because the power sector is also a dominant direct and indirect consumer of water, it is vital to understand current and likely future trends in power sector water consumption. In this paper, we use an input-output based hybrid approach to study the direct and indirect impacts on water consumption from power mix adjustment in the world's seven largest emitting economies under multiple cost-effective mitigation pathways toward the 2 °C target. Although different pathways exist, we discovered generally increases in water consumption of power sector under the long-term 2 °C target compared with no-climate-policy pathways, especially for China and India. Fulfilling the Intended National Determined Contributions (INDCs) could decouple direct water consumption and electricity output for most regions but may result in increases of indirect water consumption in China. This paper suggests that in the light of geographically uneven water scarcity, more comprehensive evaluation of both the direct and indirect water demands of the power sector is demanded when considering climate policies relevant to significant structural and technological adjustments in power sector.